Can innovative behavior be led by management? A study from the lodging business. (December 2017) - Gu, Huimin; Duverger, Philippe; Yu, Larry
Abstract: This study examined the effects of hotel management leadership on employee innovative behavior in Chinese hotel organizations. Using a dyadic sample of 164 hotel supervisors and 603 service employees at 23 four-star and five-star hotels in 11 Chinese cities, we investigated whether organizational commitment mediated the effects of leadership on employee innovative behavior. We also examined how organizational tenure moderated leadership and innovative behavior through organizational commitment. Findings from our moderated-mediation model revealed that organizational commitment mediated the relationship between leadership and innovative behavior. Similarly, organizational tenure moderated the relationship between leadership and organizational commitment: there was a stronger relationship for long-tenured employees and a weaker relationship for short-tenured employees. However, the effect of higher leadership on organizational commitment was stronger for short-tenured employees than long-tenured employees. Our results spotlight the importance of fostering organizational commitment, which directly affects innovative behavior and through which supervisors can influence individual innovative behavior. Highlights: Leadership and innovative behavior was examined using a moderated-mediation model. Leadership was not directly related to innovative behavior (IB). An indirect positive relationship was mediated by organizational commitment (OC). OC was positively and significantly associated with innovative behavior. Employee tenure moderated the relationship between leadership, OC and IB.